Assessment of the Impact of Locally Sourced Building Materials on Residential Property Development in Owerri, Imo State, Nigeria - Nwaji, O. I.; Ugonabo, C. U. (International Journal of Real Estate, 2025)
This research explores how locally sourced building materials (LSBMs) influence residential property development in Owerri, Imo State, Nigeria. Rising construction costs, lack of affordable housing, and environmental degradation stem largely from a dependence on imported, industrial materials. Through a survey of construction experts and skilled artisans in Owerri, the study gathers substantial data. It evaluates these materials based on three main criteria: their local availability, their affordability, and the resulting impact on construction expenses. Additionally, the investigation highlights common hurdles blocking LSBM utilization. These include limited policy support, negative assumptions about quality, technical skill gaps, and lack of standardisation. Encouragingly, the study finds that laterite, stone, bamboo, timber, and clay are abundantly present and inexpensive. These materials offer developers a meaningful cost reduction alternative. Although the benefits are considerable, prejudice and infrastructure gaps prevent widespread acceptance. The study urges policy, educational, and technical strategies to help close existing supply and application gaps. For lasting improvements in sustainable construction and cost efficiency, this study recommends strengthening regulatory frameworks, standardising material quality, and running education campaigns for residents and developers alike.